LIS Activities in Nepal : An Overview in prospect of DoLIA - Sapkota, Ram Kumar (Journal on Geoinformatics, Nepal, 2012)
Modern age is the age of Information Communication Technology (ICT). Every sectors are enhancing their performance, capacity and quality of job through the use of ICT. So implementing Information Communication Technology in the field of Land Administration is highly essential. Indeed it’s a need of time. On this way, in our context DoLIA is vigorously working on modernizing land administration and approaching towards paper and pencil free land administration and establishing Land Information System (LIS) in Nepal with full effort and dedication with limited manpower and resources.